From Security to Citizenship? A Study of Banser in the Reform Era - Muhammad Khoirul Muqtafa (Jurnal Identitas, 2023)
The phenomenon of Banser (militia group under Nahdlatul Ulama) in the Reform Era is quite interesting to observe. While previously, this militia’s main duty was to ensure that all activities conducted by Nahdlatul Ulama ran smoothly, this organization has now expanded its activities from countering radicalism and terrorism activities to assisting disaster management programs. This signals a new transformation within this militia group and poses serious questions about the conception of security and citizenship practices. Banser actively protects religious minority groups so that they can practice their religious activities. Different from other religious militia groups such as the Islamic Defender Front (FPI) or Moslem Paramilitary Group (Laskar Umat Islam) who often commit violent actions, Banser has their own logic of security. This logic is mainly derived from religious values they hold: moderation, justice, tolerance, and balance. How they implement these values can be seen partly from their actions to protect and reject any violence against the religious vulnerable groups. This is because they believe that violence itself is against religion. Furthermore, their actions tend to advocate a certain form of citizenship based on religious values.